Study guides

Q: Simplify this expression 4p plus 9 plus 7p plus 2 equals?

Write your answer...

Submit

Related questions

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

11-3p

It is: 11p+11 simplified

23

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

4 times p or 4p

5p x 2p = 10p, then 10p / 4p = 2 remainder 2

It is an expression that can be simplified to: 76p-5

The question contains an expression but no equation (or inequality). An expression cannot have an answer.

4p+1 = 10 4p = 10-1 4p = 9 p = 2.25

4p+9-7p+2 -3p+11 p = 11/3

p=-15

p = -1

4p+2 = 3p-7 4p-3p = -7-2 p = -9

There is no equation (nor inequality in the question and so there is nothing to solve.The expression can be simplified to 4p - 16 which can be factorised to 4*(p - 4). That is as far as you can go.

12p-15+8-4p = 89 12p-4p = 89+15-8 8p = 96 p = 12

15 + 3 = 7p - 4p ie 18 = 3p so p = 6

It is 820p2 - 4p - 32.

4P + 5O2 = 2P2O5

4p = 24 p = 6

9/4

In order to solve for p, you need to get it alone on one side of the equation4p + 7 = 94p = 2 subtract 7 from both sidesp = 2/4 divide by 4 on each sidep= 1/2 simplify

8p+2=4p-10 8p-4p=-2-10 4p=-12 p=-12/4 =-3

4p + 6 = 2 4p = -4 (subtracting 6 from both sides) p = -1 (dividing both sides by 4)

People also asked